2018
DOI: 10.1112/plms.12125
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Teichmüller geodesics in the Universal Teichmüller space

Abstract: A Thurston boundary of the universal Teichmüller space T(D) is the set of projective bounded measured laminations PMLbddfalse(double-struckDfalse) of double-struckD. We prove that each Teichmüller geodesic ray in T(D) converges to a unique limit point in the Thurston boundary of T(D) in the weak∗ topology. In particular, there is an open and dense set of geodesic rays, which have unique (weak*‐)limits in the Thurston boundary. We also show that the main result is sharp by providing an example of a Teichmüller … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In previous works [7], [8], [9], Hakobyan and the second author of this paper showed that for an integrable holomorphic quadratic differential ϕ on D, the corresponding Teichmüller geodesic of T (D) has a unique limit point on Thurston boundary of T (D). The limit point [µ ϕ ] ∈ P M L b (D) is the projective class of the transverse measure to the geodesic straightening of the vertical foliation of ϕ multiplied by the reciprocal of the length of the vertical leaves (See Remark 1.2).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…In previous works [7], [8], [9], Hakobyan and the second author of this paper showed that for an integrable holomorphic quadratic differential ϕ on D, the corresponding Teichmüller geodesic of T (D) has a unique limit point on Thurston boundary of T (D). The limit point [µ ϕ ] ∈ P M L b (D) is the projective class of the transverse measure to the geodesic straightening of the vertical foliation of ϕ multiplied by the reciprocal of the length of the vertical leaves (See Remark 1.2).…”
Section: Introductionmentioning
confidence: 87%
“…If all points on S 1 are on a finite ϕ-distance from a point in D, then as δ → 0, Γ <δ B converges to the set |ν B | of horizontal trajectories of ϕ that have one endpoint in [a, b] and the other endpoint in [c, d] (See [7]). Here, a sequence of rectifiable curves γ n converges to a curve γ if there is a uniformly Lipschitz parametrizations of all curves by the same interval so that γ n converge uniformly to γ as functions.…”
Section: Liouville Measure Of Boxes and Modulus Of Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the case when X = ∆ this map is proved to be injective by Strebel [33]. Also for X = ∆ a modular measure map (which is closely related to the horizontal measure map) is injective on the space of projective integrable holomorphic quadratic differentials with image inside the space of projective bounded measured laminations P M L b (∆) but the map is not onto (see [13]). See [34], [30], [31] or Section 2 for the definition of bounded measured laminations.…”
Section: Introductionmentioning
confidence: 99%